Halotolerant Cyanobacterium Aphanothece halophytica Contains an Na(+)-dependent F(1)F(0)-ATP Synthase with a Potential Role in Salt-stress Tolerance - Soontharapirakkul, Kanteera (American Society for Biochemistry and Molecular Biology, 2011)
Aphanothece halophytica is a halotolerant alkaliphilic cyanobacterium that can grow in media of up to 3.0 m NaCl and pH 11. Here, we show that in addition to a typical H(+)-ATP synthase, Aphanothece halophytica contains a putative F(1)F(0)-type Na(+)-ATP synthase (ApNa(+)-ATPase) operon (ApNa(+)-atp). The operon consists of nine genes organized in the order of putative subunits β, ϵ, I, hypothetical protein, a, c, b, α, and γ. Homologous operons could also be found in some cyanobacteria such as Synechococcus sp. PCC 7002 and Acaryochloris marina MBIC11017. The ApNa(+)-atp operon was isolated from the A. halophytica genome and transferred into an Escherichia coli mutant DK8 (Δatp) deficient in ATP synthase. The inverted membrane vesicles of E. coli DK8 expressing ApNa(+)-ATPase exhibited Na(+)-dependent ATP hydrolysis activity, which was inhibited by monensin and tributyltin chloride, but not by the protonophore, carbonyl cyanide m-chlorophenyl hydrazone (CCCP). The Na(+) ion protected the inhibition of ApNa(+)-ATPase by N,N′-dicyclohexylcarbodiimide. The ATP synthesis activity was also observed using the Na(+)-loaded inverted membrane vesicles. Expression of the ApNa(+)-atp operon in the heterologous cyanobacterium Synechococcus sp. PCC 7942 showed its localization in the cytoplasmic membrane fractions and increased tolerance to salt stress. These results indicate that A. halophytica has additional Na(+)-dependent F(1)F(0)-ATPase in the cytoplasmic membrane playing a potential role in salt-stress tolerance.